This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MA 36600 LECTURE NOTES: MONDAY, MARCH 2 Method of Undetermined Coefficients Undetermined Coefficients. Say that we wish to solve a constant coefficient linear second order differ ential equation in the form ay 00 + by + cy = f ( t ) We know how to find the general solution y = y ( t ) once we find homogeneous solutions y 1 = y 1 ( t ) and y 2 = y 2 ( t ), so we explain a method to find a particular solution Y = Y ( t ). Follow these three steps: #1. Express the function on the righthand side as the sum of functions f ( t ) = f 1 ( t ) + f 2 ( t ) + + f n ( t ) where each f i ( t ) is the product of a polynomial, an exponential function, and a trigonometric func tion. That is, say that we can write f i ( t ) = d i X j =0 a ij t j e i t cos i t + d i X j =0 b ij t j e i t sin i t for some constants a ij , b ij , i , and i . Note that f i ( t ) involves a polynomial of degree d i . #2. Make a guess that a solution Y i = Y i ( t ) of the nonhomogeneous equation a ( t ) Y 00 i + b ( t ) Y i + c ( t ) Y i = f i ( t ) for i = 1 , 2 , ..., n ; is in the form Y i ( t ) = d i +2 X j =0 A ij t j e i t cos i t + d i +2 X j =0 B ij t j e i t sin i t for some constants A ij and B ij . Note that i , and i are the same as above, and that Y i ( t ) involves a polynomial of degree ( d i + 2). #3. Recombine as the sum Y ( t ) = Y 1 ( t ) + Y 2 ( t ) + + Y n ( t ); then Y = Y ( t ) is the desired solution to the nonhomogeneous equation aY 00 + bY + cY = f ( t ) ....
View
Full
Document
This note was uploaded on 05/24/2011 for the course MA 36600 taught by Professor Ma during the Spring '09 term at Purdue UniversityWest Lafayette.
 Spring '09
 MA

Click to edit the document details